Association of the age and bodyweight at first calving with the reproductive and productive performance in one herd of Holstein dairy heifers in Japan. Issue 1 (15th September 2022) - Kusaka, Hiromi; Yamazaki, Takeshi; Sakaguchi, Minoru
Abstract: Background: Reducing the age at first calving (AFC) in dairy heifers may decrease replacement costs, while the acceleration of body growth could affect milk productivity. A lower bodyweight (BW) at first calving may increase calving problems and compromise the subsequent reproductive performance. Materials and methods: This retrospective study aimed to investigate the effect of AFC and BW prior to calving on milk productivity, the incidence of calving problems (difficult calving and stillbirth) and reproductive performance during the first lactation. Multivariate analysis was conducted using a total of 203 calving records from 1999 to 2012 for one herd of Holstein heifers. The AFC was categorised as young, moderate, old and very old (<22.5, 22.5 to <24.0, 24.0 to <25.5, ≥25.5 months) and the heifer BW before first calving was grouped into low, moderate, high and very high (≤625, 626–654, 655–683, ≥684 kg), respectively. Results: The incidence of difficult calving and the prevalence of stillbirth were significantly higher in the animals with low BW compared with the heifers with moderate and high BW. Even so, there was no adverse impact on reproductive performance. There was a significant association between the lifetime daily milk yield and AFC; the highest mean value for yield was recorded for the heifers in the young AFC group, which was significantly different from heifers in the moderate and old age groups. Conclusions: In this experimental herd, a reduction in AFC could increase the profitability during the first lactation.